Gut-Microbiome Composition in Response to Phenylketonuria Depends on Dietary Phenylalanine in BTBR Pahenu2 Mice - van der Goot, Els; Vink, Stefanie N.; van Vliet, Danique; van Spronsen, Francjan J.; Falcao Salles, Joana; van der Zee, Eddy A. (Frontiers in Nutrition, 2022)
Phenylketonuria is a metabolic disorder caused by a hepatic enzyme deficiency causing high blood and brain levels of the amino acid Phenylalanine, leading to severe cognitive and psychological deficits that can be prevented, but not completely, by dietary treatment. The behavioral outcome of PKU could be affected by the gut-microbiome-brain axis, as diet is one of the major drivers of gut-microbiome composition. Gut-microbiome alterations have been reported in treated PKU patients, although the question remains whether this is due to PKU, the dietary treatment, or their interaction. We, therefore, examined the effects of dietary Phenylalanine (Phe) restriction on gut-microbiome composition and relationships with behavioral outcome in mice. Male and female BTBR Pahenu2 mice received either a control diet (normal protein, "high" Phe), liberalized Phe-restricted (33% natural protein restriction), or severe Phe-restricted (75% natural protein restriction) diet with protein substitutes for 10 weeks (n = 14 per group). Behavioral performance was examined in the open field test, novel and spatial object location tests, and the balance beam. Fecal samples were collected and sequenced for the bacterial 16S rRNA region. Results indicate that PKU on a high Phe diet reduces Shannon diversity significantly and alters microbiome composition compared to wildtype animals. Phenylalanine-restriction can prevent this loss in Shannon diversity but changes community composition even more than the high-Phe diet, depending on the severity of the restriction. Moreover, on a taxonomic level, we observe the highest number of differentially abundant genera in animals that received 75% Phe-restriction. Based on correlation analyses with differentially abundant taxa, the families Entereococacceae, Erysipelotrichaceae, Porphyromonadaceae, and the genus Alloprevotella show interesting relationships with either plasma Phe levels and/or object memory. According to our results, these bacterial taxa could be good candidates to start examining the microbial metabolic potential and probiotic properties in the context of PKU. We conclude that PKU leads to an altered gut microbiome composition in mice, which is least severe on a liberalized Phe-restricted diet. This may suggest that the current Phe-restricted diet for PKU patients could be optimized by taking dietary effects on the microbiome into account.